Older Sepsis Survivors Suffer Persistent Disability Burden and Poor Long‐Term Survival - Mankowski, Robert T.; Anton, Stephen D.; Ghita, Gabriela L.; Brumback, Babette; Cox, Michael C.; Mohr, Alicia M.; Leeuwenburgh, Christiaan; Moldawer, Lyle L.; Efron, Philip A.; Brakenridge, Scott C.; Moore, Frederick A. (Journal of the American Geriatrics Society (JAGS), 2020)
Objectives Sepsis has been called a “disease of the elderly,” and as in‐hospital mortality has decreased, more sepsis survivors are progressing into poorly characterized long‐term outcomes. The purpose of this study was to describe the current epidemiology of sepsis in older adults compared with middle‐aged and young adults. Design Prospective longitudinal study with young (≤45 years), middle‐aged (46‐64 years), and older (≥65 years) patient groups. Setting University tertiary medical center. Participants A total of 328 adult surgical intensive care unit (ICU) sepsis patients. Measurements Patients were characterized by (1) baseline demographics and predisposition, (2) septic event, (3) hospital outcomes and discharge disposition, (4) 12‐month mortality, and (5) Zubrod Performance Status, physical function (Short Physical Performance Battery and handgrip strength), and cognitive function (Hopkins Verbal Learning Test, Controlled Oral Word Association, and Mini‐Mental Status Examination) at 3‐, 6‐, and 12‐month follow‐up. Loss to follow‐up was due to death (in 68), consent withdrawal (in 32), and illness and scheduling difficulties: month 3 (in 51), month 6 (in 29), and month 12 (in 20). Results Compared with young and middle‐aged patients, older patients had (1) significantly more comorbidities at presentation (eg, chronic renal disease 6% vs 12% vs 21%), intra‐abdominal infections (14% vs 25% vs 37%), septic shock (12% vs 25% vs 36%), and organ dysfunctions; (2) higher 30‐day mortality (6% vs 4% vs 17%) and fewer ICU‐free days (median = 25 vs 23 vs 20); (3) more progression into chronic critical illness (22% vs 34% vs 42%) with higher poor disposition discharge to non‐home destinations (19% vs 40% vs 62%); (4) worse 12‐month mortality (11% vs 14% vs 33%); and (5) poorer Zubrod Performance Status and objectively measured physical and cognitive functions with only slight improvement over 12‐month follow‐up. Conclusion Compared with younger patients, older sepsis survivors suffer both a higher persistent disability burden and 12‐month mortality.